IFC Annual Report 2013 : The Power of Partnerships - International Finance Corporation (Washington, DC: World Bank, 2013)
The International Financial Corporation (IFC), a member of the World Bank Group, is the largest global development institution focused exclusively on the private sector in developing countries. This report summarizes IFC’s role in helping the private sector create jobs and opportunity in developing countries. It highlights how we spur innovation, influence policy, provide a demonstration effect for others, and strive to maximize our development impact.